UPAYA MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA MELALUI MEDIA FLASHCARD DENGAN PENDEKATAN TARL PEMBELAJARAN IPAS KELAS IV SDN 124 PALEMBANG - Peni Alis Wijayanti; Putri Alawiyah; Nurul Khairunnisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine the success of the TaRL (Teaching at the Right Level) approach in enhancing engagement and learning outcomes in science and social studies (IPAS) on the topic of Plant Parts in Grade IV at SD Negeri 124 Palembang. The subjects of this research were all 37 students in Grade IV.A at SD Negeri 124 Palembang. Data analysis in this study employed a quantitative descriptive approach with percentages. This research used a classroom action research method, implementing several cycles of TaRL approach in IPAS lessons. The results indicate an increase in student engagement and learning outcomes, as evidenced by observational data: questioning activity rose from 45% in Cycle I to 79% in Cycle II, answering questions increased from 62% in Cycle I to 84% in Cycle II, expressing opinions went from 23% in Cycle I to 68% in Cycle II, and problem-solving activities grew from 40% in Cycle I to 80% in Cycle II. Based on these findings, it can be concluded that the TaRL (Teaching at the Right Level) approach can improve engagement and learning outcomes for Grade IV students in science and social studies (IPAS) on the topic of Plant Parts at SD Negeri 124 Palembang.